DISSOCIATIVE IDENTITY DISORDER TOKOH ALEX PADA FILM EMPAT MANTAN - Florita, Zahra Aulia Rezha; Salsabila, Isyana Alieffya; Jannah, Alifa Zahkrotul; Safitri, Ananda Dyah; Saputra, Muhammad Aditya (Fakultas Ushuluddin Adab dan Dakwah IAIN Lhokseumawe, 2025)
The Indonesian film industry has shown rapid development in recent years, with a variety of genres becoming increasingly diverse. One genre that has received special attention is the psychological thriller, which utilizes emotional tension and character complexity to bring the narrative to life. The film Empat Mantan by Hanny Saputra is one of the latest examples that raises the theme of Dissociative Identity Disorder (DID) or multiple personality. The film explores the impact of past trauma on the psychology of the main character, Alex, and how this condition affects his relationships with other characters, especially in the context of bullying and traumatic experiences. This study aims to describe the forms of multiple personality displayed by the character Alex in the film Empat Mantan and analyze how psychological elements are used to strengthen the storyline. With a qualitative descriptive approach, data were obtained through listening and note-taking techniques from dialogues and scenes in the film. The analysis was carried out using the theory of multiple personality and an interactive data analysis model involving data reduction, data presentation, and verification. The results of the study show that the film Empat Mantan successfully raises complex psychological issues through the depiction of various forms of multiple personality experienced by Alex. Several personalities that emerge show how this character tries to protect himself from past trauma, by creating an alternative identity that functions as a self-defense mechanism. However, the overly explicit delivery approach is considered to reduce the emotional impact and tension that should be the hallmark of the psychological thriller genre. This study contributes to understanding how psychological themes, such as DID, can be processed in film narratives to create a deeper story. In addition, this study also compares the approach of the Empat Mantan film with similar studies that examine multiple personalities, both in the context of film and literary media, to show the potential and challenges in the representation of psychological disorders in popular media. These findings are expected to provide new insights for the film industry, especially in depicting psychological disorders more subtly and effectively to enhance the emotional experience of the audience. Abstrak Industri perfilman Indonesia telah menunjukkan perkembangan pesat dalam beberapa tahun terakhir, dengan beragam genre yang semakin variatif. Salah satu genre yang mendapatkan perhatian khusus adalah thriller psikologis, yang memanfaatkan ketegangan emosional dan kompleksitas karakter untuk menghidupkan narasi. Film Empat Mantan karya Hanny Saputra menjadi salah satu contoh terkini yang mengangkat tema Dissociative Identity Disorder (DID) atau kepribadian ganda. Film ini mengeksplorasi dampak trauma masa lalu terhadap psikologi tokoh utama, Alex, dan bagaimana kondisi tersebut memengaruhi relasinya dengan karakter lain, khususnya dalam konteks perundungan dan pengalaman traumatik. Penelitian ini bertujuan untuk mendeskripsikan bentuk-bentuk kepribadian ganda yang ditampilkan oleh tokoh Alex dalam film Empat Mantan serta menganalisis bagaimana elemen psikologis digunakan untuk memperkuat alur cerita. Dengan pendekatan deskriptif kualitatif, data diperoleh melalui teknik simak dan catat dari dialog serta adegan dalam film. Analisis dilakukan menggunakan teori kepribadian ganda dan model analisis data interaktif yang melibatkan reduksi data, penyajian data, dan verifikasi. Hasil penelitian menunjukkan bahwa film Empat Mantan berhasil mengangkat isu psikologis yang kompleks melalui penggambaran berbagai bentuk kepribadian ganda yang dialami oleh Alex. Beberapa kepribadian yang muncul menunjukkan bagaimana tokoh ini berusaha melindungi dirinya dari trauma masa lalu, dengan menciptakan identitas alternatif yang berfungsi sebagai mekanisme pertahanan diri. Namun, pendekatan penyampaian yang terlalu eksplisit dinilai mengurangi dampak emosional dan ketegangan yang seharusnya menjadi ciri khas genre thriller psikologis. Penelitian ini memberikan kontribusi dalam memahami bagaimana tema psikologis, seperti Dissociative Identity Disorder (DID), dapat diolah dalam narasi film untuk menciptakan cerita yang lebih mendalam. Selain itu, kajian ini juga membandingkan pendekatan film Empat Mantan dengan penelitian-penelitian serupa yang mengkaji kepribadian ganda, baik dalam konteks film maupun media sastra, untuk menunjukkan potensi dan tantangan dalam representasi gangguan psikologis di media populer. Temuan ini diharapkan dapat memberikan wawasan baru bagi industri perfilman, khususnya dalam penggambaran gangguan psikologis secara lebih subtil dan efektif untuk meningkatkan pengalaman emosional penonton.